2021
DOI: 10.1177/14550725211009036
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter parenting and alcohol use in adolescence: A quadratic relation

Abstract: Aims: Research has underscored that an excessively intrusive parental style, defined as helicopter parenting, could be a risk factor for maladaptive behaviours in youth, including alcohol use and drug consumption. However, such at-risk behaviours have also been associated with low levels of parental involvement and warmth. Thus, the relationship between parental involvement and at-risk behaviours in adolescents is not clear. The purpose of the current study was to identify the relation between helicopter paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Although surprising, this result is not without precedent. Other studies have found curvilinear associations between parental support and adolescent substance abuse, with support predicting fewer problems up to a point, after which it was associated with more problems (e.g., Pistella et al, 2022;Stice et al, 1993). Such findings have been interpreted as a sign that parental overinvolvement can be problematic.…”
Section: Family Relationships: Change Amid Stabilitymentioning
confidence: 97%
“…Although surprising, this result is not without precedent. Other studies have found curvilinear associations between parental support and adolescent substance abuse, with support predicting fewer problems up to a point, after which it was associated with more problems (e.g., Pistella et al, 2022;Stice et al, 1993). Such findings have been interpreted as a sign that parental overinvolvement can be problematic.…”
Section: Family Relationships: Change Amid Stabilitymentioning
confidence: 97%
“…Ramstedt et al (2022) show that restrictive parental attitudes towards youth drinking may have contributed to the decline in youth drinking in Sweden. The study by Pistella and colleagues (2022), for its part, suggests that an average level of parental involvement in mothers seems to prevent adolescents from developing inordinate alcohol use patterns. This range of involvement could likely be considered characteristic of an authoritative parenting style, which is widely accepted as a predictor of the most optimal outcomes in children.…”
Section: In This Issuementioning
confidence: 99%
“…Although strict rules are generally recommended, Pistella draws attention to the risks of excessive supervision (helicopter parenting), which can have the opposite effect (Pistella et al, 2022). An overly intrusive parenting style may be a risk factor for maladaptive behavior in children, including substance abuse, especially when associated with low parental warmth and involvement.…”
Section: Introductionmentioning
confidence: 99%